Greece : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Greece. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Greece discusses that public debt is projected to trend down over the next decade, though long-term sustainability is not assured under realistic macro-fiscal assumptions. Still-weak bank balance sheets act as a drag on growth prospects and pose significant fiscal and financial stability risks. These and other factors leave Greece vulnerable to a range of external and domestic shocks. Greece's prospects for improved living standards and economic convergence within the Euro Area (EA) depend on implementing a critical mass of inter-related fiscal, financial, and structural policy reforms. In order to achieve better growth and social outcomes, the fiscal policy mix should be improved, with more emphasis on investment and targeted social spending and lower direct taxes, backed by reforms in revenue administration and public financial management. Greece's success within the currency union critically hinges on narrowing its structural competitiveness gap. Policies should focus on productivity enhancement through improved labor market flexibility, more effective labor activation policies, stronger institutions, and business deregulation.